Recombinant ROP8 antigen: diagnostics, immunogenicity, and therapeutic targeting in toxoplasmosis - Chyb, Maciej; Bekier, Adrian; Kawka, Malwina; Ferra, Bartłomiej; Dziadek, Bożena; Michlewska, Sylwia; Dzitko, Katarzyna; Trotsko, Nazar; Gatkowska, Justyna (Frontiers in Immunology, 2026)
IntroductionToxoplasma gondii invasion relies on the battery of specialized proteins, such as ROP8, which plays a key role in formation of parasitophorous vacuoles within host cells. The aim of the work was to evaluate diagnostic, immunoprophylactic and therapeutic potential of recombinant ROP8 (rROP8) protein as despite many years of research this parasitosis still is considered a significant medical and economic problem and the main areas requiring improvement are the diagnostics of the infection, vaccine development especially for humans and safe, specific chemotherapy.MethodsRecombinant ROP8 protein (rROP8) of Toxoplasma gondii was cloned, expressed in E. coli Rosetta(DE3)pLysS, and purified by nickel-affinity chromatography. Its diagnostic potential was evaluated using ELISA on sera from experimentally infected mice and human patients. The immunogenic properties of rROP8 were assessed through in vitro stimulation of human monocytes, mouse macrophages, and monocyte-derived dendritic cells, followed by cytokine profiling and co-culture with autologous CD4+ lymphocytes. Finally, drug affinity responsive target stability (DARTS) assays and confocal microscopy were used to investigate the interaction of thiazolidin-4-one derivatives with rROP8 and their inhibitory effects on parasitophorous vacuole formation.ResultsThe ROP8 proved to be promising as a potential diagnostic tool enabling the detection of specific IgG antibodies in mouse and human immune sera comparably to the native parasite antigen (TLA). The protein was also capable of activating human monocytes and mouse macrophages in vitro leading to the enhanced clearance of T. gondii tachyzoites via phagocytosis. The protein was also able to activate human monocyte-derived dendritic cells as shown by the cytometric analysis of surface markers and multiplex detection of specific cytokines, also in co-cultures with homologous lymphocytes, leading to Th1/Th17 lymphocyte phenotype. Finally, the proteolytic degradation of rROP8 was significantly inhibited by the presence of all thiazolidin-4-one derivatives, which exhibited high activity against T. gondii in previous studies.